Pulmonary Gangrene - Severe And Rare Complication Of Pneumonia - Guergana Petrova; Penka Perenovska; Dimitrinka Miteva; Radost Kabakchieva; Ognyan Brankov; Rosen Drebov (Journal of Biomedical & Clinical Research)
Pneumonia is an inflammatory lung disorder characterized by consolidation due to presence of exudates in the alveolar spaces. Most pneumonias can be effectively treated with appropriate oral antibiotics, with intravenous antibiotics being reserved for those with severe infections. We present two cases of girls admitted in our clinic with pneumonia where our conventional therapy was not sufficient. Case 1: A 15-year-old girl with cystic fibrosis, with left lobular pneumonia, for which an aggressive conservative treatment was initiated. After significant improvement, sudden detorioration and pneumothorax of the left lung occurred. She was transferred to the surgical department for intervention. Due to failure to respond to initial drainage she underwent thoracotomy and resection of the left lower lobe of the lung. The histology result confirmed gangrene. Case 2: A four-year old girl was treated for pneumonia in the right lung with aggressive intravenous antibiotic. After temporary improvement sudden deterioration was observed. The patient was transferred to the surgery department, where pulmonary gangrene was confirmed. After the lower lobe of the right lung was resected, she was discharged in good health. The careful follow up, accurate diagnosis and correct medication choice are crucial for reducing the complications of “common” pneumonia.